2002
DOI: 10.1016/s0735-1097(02)81681-3
|View full text |Cite
|
Sign up to set email alerts
|

Is the ratio of transmitral peak E wave velocity to color flow propagation velocity useful for evaluating severity of heart failure in atrial fibrillation?

Abstract: nalysis of the transmitral inflow (TMF) pattern is widely used for evaluating left ventricular (LV) diastolic function, 1,2 and provides valuable information for the management of heart failure (HF) in patients with sinus rhythm. In particular, a restrictive TMF pattern has been recognized as an ominous sign of congestive HF with high mortality. On the other hand, utilization of the TMF pattern analysis in patients with atrial fibrillation (AF) has not been established because of the lack of atrial contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…18 Noninvasive indices currently used to assess diastolic dysfunction include E/A ratio measured from the LV inflow velocity waveform by Doppler echocardiography, deceleration time of E wave and pulmonary venous blood flow waveform. [19][20][21][22] In the present study, these 2 indices were used as indices of LV diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…18 Noninvasive indices currently used to assess diastolic dysfunction include E/A ratio measured from the LV inflow velocity waveform by Doppler echocardiography, deceleration time of E wave and pulmonary venous blood flow waveform. [19][20][21][22] In the present study, these 2 indices were used as indices of LV diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…19 More recently, Oyama et al reported that the Doppler-derived index, the ratio of transmitral peak E-wave velocity to color flow propagation, correlated well with neurohumoral and hemodynamic parameters in patients with AF. 20 However, the role of tissue Doppler echocardiography in AF has not been completely established. In the present study, E/E' was found to be independently correlated with BNP level in AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the relationship between echocardiographic indexes and LV filling pressures. [5][6][7][8][9][10][11][12][13][14][15][16] However, these studies chose selected patients, such as patients with impaired LV systolic function. In the present study we investigated a wide range of LV systolic function and did not take into account the grade of diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%